A perspective of immunotherapy for acute myeloid leukemia: Current advances and challenges - Ying Chen; Ying Chen; Jishi Wang; Jishi Wang; Fengqi Zhang; Fengqi Zhang; Ping Liu; Ping Liu (Frontiers Media S.A., 2023)
During the last decade, the underlying pathogenic mechanisms of acute myeloid leukemia (AML) have been the subject of extensive study which has considerably increased our understanding of the disease. However, both resistance to chemotherapy and disease relapse remain the principal obstacles to successful treatment. Because of acute and chronic undesirable effects frequently associated with conventional cytotoxic chemotherapy, consolidation chemotherapy is not feasible, especially for elderly patients, which has attracted a growing body of research to attempt to tackle this problem. Immunotherapies for acute myeloid leukemia, including immune checkpoint inhibitors, monoclonal antibodies, dendritic cell (DC) vaccines, together with T-cell therapy based on engineered antigen receptor have been developed recently. Our review presents the recent progress in immunotherapy for the treatment of AML and discusses effective therapies that have the most potential and major challenges.